2020
DOI: 10.1038/s41598-020-60987-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved soil biological health increases corn grain yield in N fertilized systems across the Corn Belt

Abstract: Nitrogenous fertilizers have nearly doubled global grain yields, but have also increased losses of reactive N to the environment. Current public investments to improve soil health seek to balance productivity and environmental considerations. However, data integrating soil biological health and crop N response to date is insufficient to reliably drive conservation policy and inform management. Here we used multilevel structural equation modeling and N fertilizer rate trials to show that biologically healthier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 89 publications
4
32
0
Order By: Relevance
“…Application of organic residues and mulching normally increases the N mineralization potential of soils, responsible for, an increase in KMnO 4 -N 32 , 33 . Increased DHA, Ur and α / β- glu activities in mulching also pointed to the greater soil metabolic activity responsible for organic N mineralization 34 . Although mulching improved the KMnO 4 -N, it was decreased by mulching in deficit irrigation treatments.…”
Section: Discussionmentioning
confidence: 92%
“…Application of organic residues and mulching normally increases the N mineralization potential of soils, responsible for, an increase in KMnO 4 -N 32 , 33 . Increased DHA, Ur and α / β- glu activities in mulching also pointed to the greater soil metabolic activity responsible for organic N mineralization 34 . Although mulching improved the KMnO 4 -N, it was decreased by mulching in deficit irrigation treatments.…”
Section: Discussionmentioning
confidence: 92%
“…Chisanga et al, (2020) reported that there were significant differences in grain yields under different levels of NPK and application, i.e., the arrangement of fractional applications had a significant impact on crop index. Similarly, Wade et al, (2020) also reported a significant effect of nitrogen fertilizer allocation on corn grain yield. Similarly, Fernandez, (2020) reported the effects of pre-planting and nitrogen application on maize yield and found that nitrogen application before planting was significantly higher (7.6-10.6%) than before corn planting.…”
Section: Discussionmentioning
confidence: 86%
“…Conceptually, farmers see a linkage between soil health and agrochemical inputs and crop productivity. However, only a handful of studies have explored these linkages using common soil health tests (Franzluebbers 2018;Yost et al 2018;Wade et al 2020), despite farmers demonstrating a greater willingness to implement information derived from a soil test than from nontest sources (Tao et al 2012). Therefore, although the overall usage of soil health tests was low amongst farmers, the information farmers glean from those tests is both valuable and more likely to be implemented.…”
Section: Figurementioning
confidence: 99%